KARAKTERISTIK MUTU SOSIS AYAM DENGAN VARIASI SUBSTITUSI KACANG MERAH (Phaseolus vulgaris L) - Pinardi, Jaka; Widawati, Lina; Nur’aini, Hesti (University of Prof. Dr. Hazairin, SH, 2020)
Sausage is a food with a composition of meat, fat, binder, filler, water, salt, and spices and then steamed. This study aims to characterize the quality of chicken sausage substituted with red beans. The research was carried out in two stages, namely the chicken sausage processing stage and the analysis stage. The analysis conducted was protein, texture and organoleptic analysis. The results of the analysis of sausage protein levels ranged from 15.133% to 17.323%. Where the higher the red bean substitution, the lower the protein content of chicken sausage. The results of the sausage texture analysis ranged from 1,527 g/mm2 to 3,513 g/mm2. The results of the organoleptic analysis of the sausage color ranged from 2.65 (rather like) to 4.75 (really like). The results of oranoleptic analysis on the taste of sausage ranged from 2.45 (dislike) to 4.65 (really like). The results of the organoleptic analysis on the texture of the sausages ranged from 2.65 (rather like) to 4.65 (really like).